X^2-27=4x

Simple and best practice solution for X^2-27=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X^2-27=4x equation:


Simplifying
X2 + -27 = 4x

Reorder the terms:
-27 + X2 = 4x

Solving
-27 + X2 = 4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + X2 = 27 + 4x

Combine like terms: -27 + 27 = 0
0 + X2 = 27 + 4x
X2 = 27 + 4x

Simplifying
X2 = 27 + 4x

Reorder the terms:
-27 + X2 + -4x = 27 + 4x + -27 + -4x

Reorder the terms:
-27 + X2 + -4x = 27 + -27 + 4x + -4x

Combine like terms: 27 + -27 = 0
-27 + X2 + -4x = 0 + 4x + -4x
-27 + X2 + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
-27 + X2 + -4x = 0

The solution to this equation could not be determined.

 

See similar equations:

| -28x^2-36x-8=0 | | 7x-7=63 | | 2x^2+x-15=0 | | -14x^2+25x+25=0 | | 5+ax=17-bx | | 5+ax=17+-1bx | | 2x^3+3x^2-2x=3 | | 12=x+6 | | -8x^2+10x+8=0 | | 19-x=3x-1 | | -6x^2+3x+1=0 | | -2x^2+x+15=0 | | 6+9x=114 | | 8x-40=160 | | 7x^2+8x+2=0 | | 7x^2+15x+8=0 | | -3x(5x+8)= | | -5n-15+16=-3n-11 | | 30x+25x=125 | | (-10)-(-5)= | | 3x^2+10x+7=0 | | -4x^2+12x-7=0 | | 3x+5-4x=8-5x+21 | | 2+2e+m=971 | | 11x+5=6x+20 | | -4+2x=3x-8 | | X^5=x^3 | | x+19x+20=-x+62 | | 4x-7x+16x=150-7 | | 3x-8=2-5x-10 | | 5x+5=-19-7x | | -3(4-x)=18 | | 13-10x=168-45x | | 10x-5=4x+8 | | 36-5x=4x+21 | | 6x-5+x=10+x+10 | | 10x-9=4(x-1)+1 | | 87g-95g=100 | | -a+6(a+4)=3(a+5)+1 | | 95+82k-163k+78=0 | | -12x+4+5x=-7+x | | x+2x+3x=5+10+15 | | 3u^2+8u+5= | | 4[3+5(3-x)+2x]=6-2x | | 0.75b+5=128 | | 4x+5=12-3x | | x+17=-4 | | 9s^2+48s=-64 | | 3x(y+1)+3(x^2+7y)-4xy= | | x+13=4x+4 | | 4x+2=2x+10 | | 8x+1=33 | | 2x+2=6+y | | 5+5=5 | | 2x+2y=2y+x | | 3x+22=11x-66 | | y+2x=3x+y | | 11(x+8)=3(x+20) | | w^2+9w+20=0 | | 5x^2+20=0 | | 6y+3y= | | X^4+36x^2=0 | | 3[4-2(a-2)]=3(2-4a) | | 4k^2+10k=8 | | 10x+36-38x-47=0 |